Comparison of Ray Tracing and Monte Carlo Calculation Algorithms for Thoracic Spine Lesions Treated With CyberKnife-Based Stereotactic Body Radiation Therapy. (February 2016) - Okoye, Christian C.; Patel, Ravi B.; Hasan, Shaakir; Podder, Tarun; Khouri, Anton; Fabien, Jeffrey; Zhang, Yuxia; Dobbins, Donald; Sohn, Jason W.; Yuan, Jiankui; Yao, Min; Machtay, Mitchell; et al.
Stereotactic body radiation therapy (SBRT) is an emerging technology for the treatment of spinal metastases, although the dosimetric impact of the calculation method on spinal dose distribution is unknown. This study attempts to determine whether CyberKnife (CK)-based SBRT using a Ray Tracing (RyTc) algorithm is comparable dosimetrically to that of Monte Carlo (MC) for thoracic spinal lesions. Our institutional CK-based SBRT database for thoracic spinal lesions was queried and a cohort was generated. Patients were planned using RyTc and MC algorithms using the same beam angles and monitor units. Dose–volume histograms of the planning target volume (PTV), spinal cord, esophagus, and skin were generated, and dosimetric parameters were compared. There were 37 patients in the cohort. The average percentage volume of PTV covered by the prescribed dose with RyTc and MC algorithms was 91.1% and 80.4%, respectively ( P < .001). The difference in average maximum spinal cord dose between RyTc and MC plans was significant (1126 vs 1084 cGy, P = .004), with the MC dose ranging from 18.7% below to 13.8% above the corresponding RyTc dose. A small reduction in maximum skin dose was also noted ( P = .017), although no difference was seen in maximum esophageal dose ( P = .15). Only PTVs smaller than 27 cm 3 were found to correlate with large (>10%) changes in dose to 90% of the volume ( P = .014), while no correlates with the average percentage volume of PTV covered by the prescribed dose were demonstrated. For thoracic spinal CK-based SBRT, RyTc computation may overestimate the MC calculated average percentage volume of PTV covered by the prescribed dose and have unpredictable effects on doses to organs at risk, particularly the spinal cord. In this setting, use of RyTc optimization should be limited and always verified with MC.